Integration Technology and Learner-Centred Approaches for Better Generation Z’s English Reading Skills: A Literature Review - Yuni Putri Utami; Rachmad Hidayat; Nurul Fadhilah (PT. Inovasi Teknologi Komputer, 2024)
Gen Z is a generation of individuals that were born and raised in an era where technology was prevalent and accessible from a young age, making them highly proficient in digital skills. This generation has a certain quality when it comes to acquiring English language skills. This study seeks to examine strategies for enhancing the reading proficiency of Generation Z through the incorporation of technology and learner-centred instructional approaches. This research employed a literature review methodology to summarise and synthesise theories from reputable academic sources. The aim of this research was to address the challenges and opportunities that Gen Z teachers face when teaching English reading skills. In addition to discovering and investigating efficient techniques for enhancing English reading proficiency, The research utilises many scholarly sources, such as journal articles, conference proceedings, books, and theses, in the domain of English language teaching and learning. The findings of this literature review indicate that using technology and adopting a learner-centred approach are crucial for stimulating the interest and engagement of Generation Z in English reading instruction.